Serum Zinc Level in Preterm Low Birth Weight Babies and Its Comparison between Preterm AGA and Preterm SGA Babies - Islam, MN; Ullah, MW; Siddika, M; Qurishi, SB; Hossain, MA; Choudhury, MA; Akhter, S (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):145-8.The abstract of this article is available on the PubMed website